Dysregulated methylation of the human BOLL promoter hinders germ cell development from spermatogonia to spermatids - Tsung-Yen Lin; Hsing-Yi Chen; Yung-Hsuan Cheng; Chun-Wun Lu; Hsiu-Yen Ma; Hsiu-Chiung Hou; Yung-Ming Lin; Shih-Chieh Lin; Yu-Sheng Cheng (Molecular Biology Reports, 2026)

Significant crust-thinning beneath the Ilan Plain of Taiwan for revealing westward impingement of the Okinawa Trough opening into Taiwan Orogeny - Ya-Chuan Lai; Cheng-Horng Lin; Min-Hung Shih; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Tectonophysics, 2026)

Infragravity oscillations in a coupled-basin marina under typhoon conditions: physical model experiments and numerical modeling - Shih-Feng Su; Chia-Hsuan She; Jia-Lin Chen; Chen-Hsun Wei; Zhi-Cheng Huang (Ocean Engineering, 2026)

Uncovering an aseismic slab for showing the flipping of subduction polarity in the Taiwan area - Lin Cheng-Horng; Min-Hung Shih; Ya-Chuan Lai; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Journal of Asian Earth Sciences, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Non-overtly damaging cold atmospheric plasma induces adaptive epidermal molecular responses associated with integrin alpha 6 - Yu-Ping Cheng; Hua-Lin Chen; Yu-Hsuan Chen; Chang-Sheng Chen; Kuan-Wei Lee; Jong-Shinn Wu; Yun-Chien Cheng; Shih-Chang Lin; Jiun-Wen Guo (Chemico-Biological Interactions, 2026)

Automated computer vision monitoring of black soldier fly larval growth using metaheuristic optimization for waste-to-feed bioconversion - Jui-Sheng Chou; Benjawan Phakdee; Zih-Tong Lin; Chang-Ping Yu; Pei-Hsun Wu; Cheng-jen Shih (Computers and Electronics in Agriculture, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

IoT-based automated monitoring and assessment of tea shoot density using canopy imaging - Hsin-Cheng Chen; Shih-Fang Chen; Shiou-Ruei Lin; Ta-Te Lin (Computers and Electronics in Agriculture, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Host acetyl-CoA pathways support WSSV replication - Shu-Wen Cheng; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Exploring the anticancer potential of Polygonum barbatum (L.) against colorectal cancer: In vitro and in vivo investigations - Pi-Kai Chang; I-Chuan Yen; Wei-Cheng Tsai; Kuen-Tze Lin; Shih-Yu Lee (Phytochemistry Letters, 2025)

From soft to hard adventure: Examining experienced mountaineers’ mountaineering intentions through the lens of the theory of planned behavior - Shih-Shuo Yeh; Tai-Ying Chiang; Kuan-Ying Chen; Chen-Lin Lee; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Eco-friendly synthesized zeolitic imidazolate framework-8 enables one-step cerium recovery from water - Ying Zhou; Shengshou Ma; Purui Lin; Changzhong Liao; Cheng-Wei Kao; Miaoling Chen; Minhua Su; Kaimin Shih (Chemical Engineering Journal, 2024)

Measuring Spatial Radiation Dose Distribution During Abdominal Computed Tomography Scanning with Optically Stimulated Luminescence Dosimeters - Wen-Chuan Chang; Tian-Yu Shih; Pei-Ren Fang; Cheng-Hsun Lin (Journal of Medical and Biological Engineering, 2024)
Purpose As the proportion of medical radiation exposure increases, the exposure dose has received increasing attention. When performing interventional radiological diagnosis, examiners are often exposed to radiation. Therefore, patients and medical personnel are exposed to higher amounts of radiation dose. Accordingly, we used optically stimulated luminescence dosimeters (OSLDs) to measure the ambient air kerma during abdominal CT scanning to observe the spatial distribution of the doses. Methods An abdominal CT scan under a voltage of 120 kVp was performed, and OSLDs were used for the measurement. The measurement range extended from the examination couch that serves as the center point to the walls and was divided into four areas. The OSLD measurements were undertaken at three different heights (i.e., 85, 140, and 150 cm from the floor) for spatial dose detection. The OSLDs were fixed up to lines at the three height levels. Each dosimetry point was 50 cm apart. In addition, the surface incident doses of the prosthesis's mammary gland, liver, and gonad were estimated. Results According to the spatial dose distribution at the three different heights, the maximum dose and minimum dose in front of the bore were 0.194 ± 0.008 and 0.006 ± 0.001 mGy, respectively; 2 m away from the bore, the dose reduced to 9% of the maximum dose. The surface incident doses of the mammary gland, liver, and gonad were 1.321 ± 0.121, 13.083 ± 0.642, and 13.441 ± 0.658 mGy, respectively. Conclusion The spatial dose distribution revealed that the dose was the highest at the height of 140 cm and in front of the bore. The dose on the left side was higher than that on the right side. In addition, the dose was inversely proportional to the square of the distance. If the examiners must perform interventional radiological diagnosis during CT scanning, they should put on radiation protection equipment and stand behind the bore to minimize the radiation exposure.

The changes and the potential clinical applications of cytokines in Taiwan’s major venomous snakebites patients - Chih-Chuan Lin; Chia-Cheng Wang; Chun-Hsiang Ou Yang; Chien-Chun Liu; Jau-Song Yu; Wen-Chih Fann; Yen-Chia Chen; Chia-Pang Shih (Toxicon, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

A modified lift-off test for restressing anchors of a rehabilitated landslide slope - Shih-Hao Cheng; Kuo-Hsin Yang; Shih-Yuan Lin; Chen-Kan Liao; Hung-Jiun Liao (Landslides, 2024)

Role of artificial intelligence in carbon cost reduction of firms - Cheng-Jui Tseng; Shih-Yen Lin (Journal of Cleaner Production, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Acoustic Field Radiation Prediction and Verification of Underwater Vehicles under a Free Surface - Yung-Wei Chen; Cheng-Cheng Pan; Yi-Hsien Lin; Chao-Feng Shih; Jian-Hong Shen; Chun-Ming Chang (Journal of Marine Science and Engineering, 2023)
This study aimed to examine the acoustic field radiated by propellers and underwater vehicles. For the verification of sound radiation in underwater vehicles, numerical methods are widely used in addition to experiments and propeller blade frequencies for calculation and validation. Numerical convergence and accuracy are more important for near-field and far-field problems. This paper uses the boundary element method (BEM) to assess the convergence of the finite volume method (FVM). In this study, the FVM, including the Reynolds-averaged Navier–Stokes method and the Ffowcs Williams–Hawkings (FW-H) acoustic model, is used to investigate the influence of various geometric inflows on the hydrodynamic and noise performance of the propeller. Then, the sound radiation of the FVM is compared with the BEM at the far field to determine the number of meshed elements. Furthermore, spectral analysis is being conducted to examine the noise generated by the underwater vehicle and propeller. The objective is to investigate the influence of the free surface on propeller efficiency. After verifying the numerical simulation, the results indicate that a relationship can be established between water pressure and propeller thrust under specific conditions. This relationship can be used to estimate the magnitude of propeller thrust at different water depths. The simulated results of propeller thrust, torque coefficient, propulsion efficiency, and sound radiation in this study are consistent with experimental values. This demonstrates the accuracy and practicality of the findings of numerical procedures in engineering applications.

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Xenoestrogen Status of Wuling Farm to Surrounding Water Bodies: An Application of Biochemical Parameters Using Onychostoma barbatulum - Lin-Yan Liao; Hui-Ling Cheng; Shu-Yin Wang; Shih-Hsiung Liang; Da-Ji Huang (Journal of Marine Science and Engineering, 2022)
The aim of this study was to apply biochemical parameters to Onychostoma barbatulum to understand whether Wuling Farm activities have caused organic pollution from xenoestrogens to flow into surrounding streams and thereby affected area aquatic ecosystems. Individuals of the Taiwan shovel-jaw carp (O. barbatulum) were collected by fyke netting in the Cijiawan, Kaoshan, and Yusheng Rivers in the protected area of Shei-Pa National Park and in the Ikawan River outside the protected areas from 4–5 June 2015 to 20–21 September 2015. The collected male individuals of O. barbatulum were divided into two groups. In the first group monooxygenase (Mon) activity, glutathione S-transferase (GST) activity, and vitellogenin (VTG) concentration in the liver were measured right after they were captured. Those in the second group were acclimated for 14 days and then exposed to 0 (control) or 10 ng/L 17β-estradiol for 10 days and then measured for changes in Mon, GST, and VTG in their livers. The value of VTG concentrations in O. barbatulum individuals collected from the Ikawan River was 2.12 ± 1.62 μg PO42+/g protein, which was the highest among all samples, followed by those collected from the Yusheng River (0.78 ± 1.00 μg PO42+/g protein). Individuals collected from the Yusheng River had the highest liver Mon activity (4.16 ± 1.08△A650/30 min/g protein) and the highest GST activity (1.58 ± 1.13 △A340/20 min/g protein), followed by those from the Ikawan River (Mon: 3.63 ± 1.13 △A650/30 min/g protein; GST: 1.24 ± 0.73 △A340/20 min/g protein). Comprehensive analyses showed that Mon and GST activities and VTG concentrations in livers measured right after being collected were lower than individuals exposed to 10 ng 17β-estradiol/L in the laboratory. Induced VTG concentrations were 9.87 ± 0.89 μg PO42+/g protein, Mon activity 8.02 ± 1.74 △A650/30 min/g protein, and GST activity 3.24 ± 0.62 △A340/20 min/g protein, indicating that farming activities have not significantly affected these aquatic organisms. However, pollution sources are still releasing pollutants containing xenoestrogens into the Yusheng River and Ikawan River. The impact of xenoestrogens is worthy of continuous long-term follow-up monitoring.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Development of a Direction-Oriented Motion and Short-Sitting and Lying Tai Chi (DOM-SSLTC) Model for Function Recovery in Stroke Patients - Lian-Hui Lee; Hwai-Ting Lin; Nai-Wen Tsai; Yung-Chieh Yen; Cheng-Hsien Lu; Chun-Chung Lui; Hsien-Ming Chung; Kun-Chang Tsai; Shih-Pin Hsu; Huan-Wen Tsui (Journal of Medical and Biological Engineering, 2019)

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Toward a higher yield: a wireless sensor network-based temperature monitoring and fan-circulating system for precision cultivation in plant factories - Joe-Air Jiang; Min-Sheng Liao; Tzu-Shiang Lin; Chen-Kang Huang; Cheng-Ying Chou; Shih-Hao Yeh; Ta-Te Lin; Wei Fang (Precision Agriculture, 2018)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Assessment of Land Subsidence and Climate Change Impacts on Inundation Hazard in Southwestern Taiwan - Hsiao‐Wen Wang; Cheng‐Wei Lin; Chun‐Yao Yang; Chung‐Feng Ding; Hwung‐Hweng Hwung; Shih‐Chun Hsiao (Irrigation and Drainage, 2018)
Excessive extraction of groundwater resulting in serious land subsidence as well as intensified rainfall and storm surges due to climate change complicate the flooding problems in southwest Taiwan. A coupled set of different models was proposed to analyze the effect of inundation risk considering land subsidence and climate change. Three models, including the groundwater flow model, land subsidence model, and the physiographic drainage–inundation model, were used in this study, enabling simulations of different considerations. The results revealed that more severe flooding would result from land subsidence and climate change. The findings of a 21% increase in flood area with an inundation depth greater than 1.5 m for 200‐yr return period events clearly showed more severe flooding would result from land subsidence. The flooding in those severely subsiding areas would increase in a range from 3.4 to 21.5% when further considering climate change. While the simulation results revealed that the flood area could be decreased by as much as 50% taking into account the implemented policies, the coastal region would still be exposed to a high risk of being flooded. It thus suggests that policies focusing on infrastructure would be insufficient, and river basin management as well as spatial planning should be investigated further. Copyright © 2018 John Wiley & Sons, Ltd.

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Sediment control function of river notches - Chia-Hsing Lin; Cheng-Ju Liu; Shih-Hsun Lin; Chjeng-Lun Shieh (Journal of Mountain Science, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Serotonin Receptor 2B Mediates Mechanical Hyperalgesia by Regulating Transient Receptor Potential Vanilloid 1 - Yeu-Shiuan Su; Yuan-Yi Chiu; Shih-Yuan Lin; Chih-Cheng Chen; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Increased relative risk of acute pancreatitis in zolpidem users - Shih-Wei Lai; Cheng-Li Lin; Kuan-Fu Liao (Psychopharmacology, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

High seroprevalence of human herpesvirus type 8 infection in males with advanced lung carcinoma - Cheng-Chuan Su; Chun-Liang Lai; Shih-Ming Tsao; Ming-Nan Lin; Tang-Yuan Chu (Medical Microbiology and Immunology, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

Suppression of PI3K/Akt signaling by synthetic bichalcone analog TSWU-CD4 induces ER stress- and Bax/Bak-mediated apoptosis of cancer cells - Meng-Liang Lin; Shih-Shun Chen; Ren-Yu Huang; Yao-Cheng Lu; Yu-Ren Liao; Mopuru Vijaya Bhaskar Reddy; Chuan-Chun Lee; Tian-Shung Wu (Apoptosis, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Changes in the potential habitats of 10 dominant evergreen broad-leaved tree species in the Taiwan-Japan archipelago - Katsuhiro Nakao; Motoki Higa; Ikutaro Tsuyama; Cheng-Tao Lin; Shih-To Sun; Jian-Rong Lin; Chyi-Rong Chiou; Tzu-Ying Chen; Tetsuya Matsui; Nobuyuki Tanaka (Plant Ecology, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Effect of particle size of titanium dioxide nanoparticle aggregates on the degradation of one azo dye - Yang-hsin Shih; Cheng-han Lin (Environmental Science and Pollution Research, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Acacetin inhibits the invasion and migration of human non-small cell lung cancer A549 cells by suppressing the p38α MAPK signaling pathway - Shang-Tao Chien; Su-Shun Lin; Cheng-Kun Wang; Yuan-Bin Lee; Kun-Shiang Chen; Yao Fong; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2011)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

An integrated approach for identification of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) pollutant sources based on human blood contents - Yu-Cheng Chen; Perng-Jy Tsai; Lin-Chi Wang; Minliang Shih; Wen-Jhy Lee (Environmental Science and Pollution Research, 2010)

Ameliorative effects of Vaccaria segetalis extract on osteopenia in ovariectomized rats - Chun-Ching Shih; Cheng-Hsiu Lin; Wei-Li Lin (Journal of Natural Medicines, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Potential refugia in Taiwan revealed by the phylogeographical study of Castanopsis carlesii Hayata (Fagaceae) - YU‐PIN CHENG; SHIH‐YING HWANG; TSAN‐PIAO LIN (Molecular Ecology, 2005)
In this study, we examined spatial patterns of chloroplast DNA (cpDNA) variation in a total of 30 populations of Castanopsis carlesii Hayata (Fagaceae), a subtropical and temperate tree species, including 201 individuals sampled throughout Taiwan. By sequencing two cpDNA fragments using universal primers (the trn L intron and the trn V‐ trn M intergenic spacer), we found a total of 1663 bp and 21 polymorphic sites. These gave rise to a total of 28 cpDNA haplotypes. The level of differentiation among the populations studied was relatively high ( G ST = 0.723). Two ancestral haplotypes are widely distributed. The Central Mountain Ridge (CMR) of Taiwan represents an insurmountable barrier to the east–west gene flow of C. carlesii . Among the populations studied, three separated populations, at Lienhuachih, Fushan and Lichia, have high nucleotide diversity. Estimates of N ST – G ST for populations on both sides of the CMR indicate that no phylogeographical structure exists. According to the genealogical tree, number of rare haplotype and population genetic divergence, this study suggests that two potential refugia existed during the last glaciation: the first refugium was located in a region to the north of Hsuehshan Range (HR) and west of the CMR; the second refugium was located in south, especially southeastern Taiwan. In fact, the second refugium happens to be the same as that reported for Quercus glauca . A ‘star‐like’ genealogy is characteristic when all haplotypes rapidly coalesce and is a general outcome of population expansion. The neutrality test and mismatch distribution also suggest demographic expansion recovering from a bottleneck.

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)